Comparing primary caregivers’ reported injury data with routinely recorded injury data to assess predictors of childhood injury - Luam Ghebreab; Bridget Kool; Arier Lee; Susan Morton (BMC Medical Research Methodology, 2023)
Abstract Background Linking self-reported data collected from longitudinal studies with administrative health records is timely and cost-effective, provides the opportunity to augment information contained in each and can offset some of the limitations of both data sources. The aim of this study was to compare maternal-reported child injury data with administrative injury records and assess the level of agreement. Methods A deterministic linkage was undertaken to link injury-related data from the Growing up in New Zealand (GUiNZ) study to routinely collected injury records from New Zealand’s Accident Compensation Corporation (ACC) for preschool children. The analyses compared: (i) the characteristics of mothers with linked data vs. those without, (ii) injury incidences from maternal recall with those recorded in ACC injury claims, and (iii) the demographic characteristics of concordant and discordant injury reports, including the validity and reliability of injury records from both data sources. Results Of all mothers who responded to the injury questions in the GUiNZ study (n = 5836), more than 95% (n = 5637) agreed to have their child’s record linked to routine administrative health records. The overall discordance in injury reports showed an increasing trend as children grew older (9% at 9 M to 29% at 54 M). The mothers of children with discordance between maternal injury reports and ACC records were more likely to be younger, of Pacific ethnicity, with lower educational attainment, and live in areas of high deprivation (p < 0.001). The level of agreement between maternal injury recall and ACC injury record decreased (κ = 0.83 to κ = 0.42) as the cohort moved through their preschool years. Conclusions In general, the findings of this study identified that there was underreporting and discordance of the maternal injury recall, which varied by the demographic characteristics of mothers and their child’s age. Therefore, linking the routinely gathered injury data with maternal self-report child injury data has the potential to augment longitudinal birth cohort study data to investigate risk or protective factors associated with childhood injury.